2022
DOI: 10.1007/s13205-022-03281-5
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies: a remedial approach to prevent SARS-CoV-2 infection

Abstract: SARS-CoV-2, the newly emerged virus of the Coronaviridae family is causing havoc worldwide. The novel coronavirus 2019 was first reported in Wuhan, China marked as the third highly infectious pathogenic virus of the twenty-first century. The typical manifestations of COVID-19 include cough, sore throat, fever, fatigue, loss of sense of taste and difficulties in breathing. Large numbers of SARS-CoV-2 infected patients have mild to moderate symptoms, however severe and life-threatening cases occur in about 5–10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…COVID-19 is a public health emergency of global concern. A large number of SARS-CoV-2-infected patients exhibit a mild-to-moderate illness, about 5-10% of the infections occur serious and life-threatening cases, and the mortality rate is about 2% [37]. The number of new confirmed patients continues to increase, highlighting the importance of the development of rapid and effective therapeutic strategies by the design of new specific drugs or the repurposing of existing drugs [38].…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…COVID-19 is a public health emergency of global concern. A large number of SARS-CoV-2-infected patients exhibit a mild-to-moderate illness, about 5-10% of the infections occur serious and life-threatening cases, and the mortality rate is about 2% [37]. The number of new confirmed patients continues to increase, highlighting the importance of the development of rapid and effective therapeutic strategies by the design of new specific drugs or the repurposing of existing drugs [38].…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Sotrovimab, a cutting-edge monoclonal antibody therapy, has been designed to inhibit the activity of the virus responsible for COVID-19. Regrettably, a multivariable clinical trial revealed that both sotrovimab and BRII-196/BRII-198 can not demonstrate any effective clinical outcomes in hospitalised COVID-19 adult patients 104,105. Intriguingly, as the first medication to receive FDA authorisation for pre-exposure prophylaxis of COVID-19, Evusheld has undergone a revision in its Emergency Use Authorisation (EUA) by the FDA, increasing the recommended dosage to enhance its preventive efficacy.…”
mentioning
confidence: 99%